Effect of Calcium Carbonate as Filler at the Chitosan/Calcium Carbonate Composite Membrane - Retno Rahayu Dinararum; Dian Permana; Lukman Atmaja (Institut Teknologi Sepuluh Nopember, 2015)
Chitosan; calcium carbonate; DMFC; thermal stability Membrane is the most important part of Direct Methanol Fuel Cell (DMFC) because of its function as a proton transfer. The purpose of this research was studying the effect of calcium carbonate filler to the performance of chitosan (CS)/Calcium Carbonate (CC) composite membrane using 0.02; 0.04; 0.06; 0.08; and 0.10 g of CC. In this study, CS/CC membranes showed high performance for DMFC application. The best concentration of CS/CC was obtained with 0.06 g of CC based on proton conductivity, methanol permeability, and TGA measurements.